1999
DOI: 10.1007/bf02979153
|View full text |Cite
|
Sign up to set email alerts
|

Stability and cytotoxicity of Fab-ricin A immunotoxins prepared with water soluble long chain heterobifunctional crosslinking agents

Abstract: The effects of the hindered and non-hindered water soluble long-chain disulfide bonds on the stability and cytotoxicity of the ricin A chain (RTA) immunotoxin were examined. The RTA immunotoxins were prepared with the Fab fragments of anti-common acute lymphoblastic leukemia antigen (CALLA) monoclonal antibody (Fab-RTA) using sulfosuccinimidyl-6-[(-methyl-(-(2-pyridyldithio)toluamido]hexanoate (S-LC-SMPT) and sulfosuccinimidyl-6-[3-(2-pyridyldithio)-propionamido]hexanoate (S-LC-SPDP). The prepared Fab-RTA immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The relatively fast cleavage of disulfide linkages in solution was also noted when others prepared disulfide-linked immuno-toxins (i.e., conjugates prepared by conjugating a targeting moiety such as an antibody to a cell-surface molecule and a drug exhibiting cellular toxicity). 26,27 Constrained disulfide linkages were proposed as a means to minimize the linkage cleavage in this case. 26,27 The fast * This analysis relies on an indirect assessment of the extent of thiolBP substitution for HA-bound conjugates.…”
Section: Cleavage Of Hydroxyapatite-bound Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively fast cleavage of disulfide linkages in solution was also noted when others prepared disulfide-linked immuno-toxins (i.e., conjugates prepared by conjugating a targeting moiety such as an antibody to a cell-surface molecule and a drug exhibiting cellular toxicity). 26,27 Constrained disulfide linkages were proposed as a means to minimize the linkage cleavage in this case. 26,27 The fast * This analysis relies on an indirect assessment of the extent of thiolBP substitution for HA-bound conjugates.…”
Section: Cleavage Of Hydroxyapatite-bound Conjugatesmentioning
confidence: 99%
“…26,27 Constrained disulfide linkages were proposed as a means to minimize the linkage cleavage in this case. 26,27 The fast * This analysis relies on an indirect assessment of the extent of thiolBP substitution for HA-bound conjugates. The necessary values were obtained from the generated %HA binding data [ Fig.…”
Section: Cleavage Of Hydroxyapatite-bound Conjugatesmentioning
confidence: 99%
“…However, as GnRH is a relatively small peptide compared with many large cell recognition molecules such as IgG, GnRH‐cytotoxins may exit the endosome and enter the cytoplasm without being cleaved. Even when large targeting agents are used, evidence is mounting that stable linkers should be considered in conjugate design, including hindered disulfide‐bond linkers, modified short‐chain (Gly‐Phe‐Leu‐Gly) linker, and poly(ethylene glycol)‐dipeptidyl linkers 27–30 . For instance, Cumber et al 31 and Woo et al 29 demonstrated that hindered disulfide‐bonds in immunotoxins had enhanced stability (threefold more stable) compared with non‐hindered disulfide‐bonds.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials using immunotoxins have led to studies regarding their optimization focused on both target and toxic domains, although the target domain is the one which has evolved more over the years . Thus, immunotoxins were initially designed containing the entire antibody which soon was replaced by the Fab domain, the single chain variable fragment (scFv) or even solely two antibody complementary determinant regions, aiming to achieve size optimization . Along with these studies, others have focused on the stability of the construct , the use of different coadjuvants or modifications to improve specificity by combining two or more different binding domains to obtain diabodies or triabodies .…”
Section: Introductionmentioning
confidence: 99%